2015
DOI: 10.1093/jisesa/iev117
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy ofPlectranthus glandulosus(Lamiaceae) andCallistemon rigidus(Myrtaceae) Leaf Extract Fractions toCallosobruchus maculatus(Coleoptera: Bruchidae)

Abstract: As part of on-going efforts to use eco-friendly alternatives to chemical pesticides, methanol crude extracts of Plectranthus glandulosus and Callistemon rigidus leaves were sequentially fractionated in hexane, chloroform, ethyl acetate, and methanol to establish the most active fraction(s) against Callosobruchus maculatus in cowpea. Cowpea seeds (25 g) were treated with 0.5, 1, 2, and 4 g/kg of extract to evaluate the contact toxicity and F1 progeny production of the beetles in the laboratory. Mortality was re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 23 publications
3
14
0
1
Order By: Relevance
“…The presence of the epoxy group was further confirmed by the HMBCs between H-C(2 0 ) and C(3 0 )/C(4 0 ), and between H-C(1 0 ) and C(4a 0 )/C(9a 0 ), as well as the 1 H, 1 H-COSY spin system of H-C(1 0 )/H-C(2 0 )/H-C(3 0 )/H-C(4 0 )/H-C(4a 0 ) ( Figure 2). In addition, the HMBCs between OH (d(H) 9.75 (1 H, s)) and C (6), between H-C(13)/H-C (14) and C(5), between OH (d(H) 15.33 (1 H, s)) and C(6 0 ), and between H-C (7) and C(7 0 ) suggested these two hydroxy groups were attached at C(5) and C(7 0 ) positions, respectively. Thus, the planar structure of 1 was assigned as shown in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The presence of the epoxy group was further confirmed by the HMBCs between H-C(2 0 ) and C(3 0 )/C(4 0 ), and between H-C(1 0 ) and C(4a 0 )/C(9a 0 ), as well as the 1 H, 1 H-COSY spin system of H-C(1 0 )/H-C(2 0 )/H-C(3 0 )/H-C(4 0 )/H-C(4a 0 ) ( Figure 2). In addition, the HMBCs between OH (d(H) 9.75 (1 H, s)) and C (6), between H-C(13)/H-C (14) and C(5), between OH (d(H) 15.33 (1 H, s)) and C(6 0 ), and between H-C (7) and C(7 0 ) suggested these two hydroxy groups were attached at C(5) and C(7 0 ) positions, respectively. Thus, the planar structure of 1 was assigned as shown in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the planar structure of 1 was assigned as shown in Figure 2. The relative configuration of 1 was established by the NOESY cross peaks between H-C(9) and H-C (14), between H-C(10) and H-C(18 0 ), between H-C(4a 0 ) and H b -C(4 0 )/H-C(13 0 )/H-C(18 0 ), between H b -C(4 0 ) and H-C(12 0 ), as well as between H-C(2 0 ) and H-C(3 0 ) ( Figure 3). Fortunately, suitable crystals of 1 were obtained in methanol solution, and a single crystal X-ray diffraction experiment (CuK a radiation) was carried out.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some compounds including one methoxylated flavonoid derivative, plectranmicin, and one monoterpene derivative, plectranmicinol, together with seven known compounds including 5-hydroxy-3,7,2′,4′tetramethoxyflavone; 5,7-dihydroxy-3,2′,4′-trimethoxyflavone; 7-hydroxy-5,6,4′-trimethoxyflavone; 3-epi-betulinic acid; 3- O - β -D-glucopyranosyl; stigmasterol; β -sitosterol, and 4-epi-fridelin were isolated from the whole plant of the studies species [ 20 ]. Earlier biological studies reported the antinociceptive and anti-inflammatory effects [ 21 ] as well as the antioxidant and insecticidal activities of P. glandulosus [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%